1995
DOI: 10.1029/94jb00937
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale landslide simulations: Global deformation, velocities and basal friction

Abstract: The cause of the apparent small friction exhibited by long rtmout landslides has long been speculated upon. In an attempt to provide some insight into the matter, this paper describes results obtained from a discrete particle computer simulation of landslides composed of up to 1,000,000 two-dimensional discs. While simplified, the results show many of the characteristics of field data (the volumetric effect on rtmout, preserved stra'ta, etc.) and with allowances made for the two-dimensional nature of the simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
241
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 266 publications
(257 citation statements)
references
References 28 publications
16
241
0
Order By: Relevance
“…We note that landslide observations occur after the slide has come to rest. Thus, the observational relationships indicating low basal friction [e.g., Coe et al, 2016] are consistent with the late time behavior of the slides simulated by Campbell et al [1995].…”
Section: Modern Slides Have Diverse Compositionsupporting
confidence: 58%
See 2 more Smart Citations
“…We note that landslide observations occur after the slide has come to rest. Thus, the observational relationships indicating low basal friction [e.g., Coe et al, 2016] are consistent with the late time behavior of the slides simulated by Campbell et al [1995].…”
Section: Modern Slides Have Diverse Compositionsupporting
confidence: 58%
“…Other examples are the Karakoram slides [Hewitt, 1988[Hewitt, , 2002Hewitt et al, 2008], the Socompa slide [Wadge et al, 1995], the Köfels slide [Erismann, 1979], Madison Canyon [Hadley, 1964], Black Canyon, and El Capitan and Split Mountain slides [Yarnold and Lombard, 1989].) Campbell et al [1995] demonstrated that stratigraphy preservation is the result of a folding process during which the entire landslide is shearing, requiring a friction reduction mechanism that acts globally, not just in a basal layer. Only very near the end of sliding did these authors observe shear localized at the base.…”
Section: Modern Slides Have Diverse Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In this paper we use a traditional DEM approach similar to that presented by Cleary and Campbell [1993]; Campbell et al [1995]; Morgan [1999]; Morgan and Boettcher [1999], based on an existing two-dimensional DEM application [Rege, 1996;Williams and Rege, 1997].…”
Section: Discrete Element Methodsmentioning
confidence: 99%
“…[6] This work investigates hydromechanical behavior of porous media using a DEM technique for solid mechanics first presented by Cundall [1971] and Cundall and Strack [1979], which has successfully approximated the behavior of noncohesive, granular systems under low stress conditions [Cundall et al, 1982;Cleary and Campbell, 1993;Campbell et al, 1995;Morgan, 1999;Morgan and Boettcher, 1999], and lithified sedimentary rocks [Bruno and Nelson, 1991;Potyondy et al, 1996;Hazzard et al, 2000;Boutt and McPherson, 2002]. Extensive comparisons of the DEM to theoretical, numerical, and experimental systems have been performed [Pande et al, 1990].…”
Section: Modeling Approachmentioning
confidence: 99%